The coming of age of digital technologies in global health within the Indian context: a review - Vivek N. Dileep (SpringerOpen, 2024)
Abstract Digital approaches have been recognized as an essential instrument for improving health systems to fulfill the Sustainable Development Goals (SDGs) and the targets for universal health care. This review article discusses policy and regulatory developments in the arena of digital health, at the global level, with a particular focus on India. It also points out that there is a need for convergence among industry, policymakers, and civil society in addressing issues of privacy and accessibility to all individuals who require affordable and quality healthcare. For the best use of digital services, inter-sectoral collaboration is necessary to integrate organizational, human, financial, and technological resources.